Factors affecting students' career choice in economics majors in the COVID-19 post-pandemic period: A case study of a private university in Vietnam - Nguyen Trong Luan; Nguyen Huu Tri; Nguyen Ngoc Han; Nguyen Dai Loi; Nguyen Thi Thu Dao; Le Duy Linh (Journal of Innovation & Knowledge (JIK), 2023)
The requirement for quantity and quality of human resources, especially occupations in the economics field, has played a significant role in recovering and improving the COVID-19 pandemic economic situation in Vietnam. Therefore, this encouraged economics majors to attract a large number of students to enrol in 2021. This study aims to determine the factors affecting the career choices of economic students in Vietnam. The research focuses on analysing six factors to determine the relationship between variables that help explain students' compatibility and their chosen majors. A survey questionnaire using simple random sampling collected 309 data points from economics students at a private university in Vietnam. Methodologies such as Cronbach's Alpha, exploratory factor analysis, confirmatory factor analysis, regression, and structural equation modelling were employed using SPSS and Amos software to check the correlation between factors and draw conclusions about factors affecting students' career choices. The results revealed that influencers, interests, financial resources and career opportunities were critical elements that influenced students' decisions in choosing a major. Interest (to pursue passion) was considered by students in choosing a major - which could also encourage them to develop their own capabilities. Additionally, the data proved that most job selections were based on future employability; therefore, career opportunities had the most positive impact on students' decisions. The findings of this study identify determinants of students' choice in economics majors and their relationships and can improve students' awareness and future orientation before deciding to choose a major. Moreover, this study provides valuable data for universities to formulate and develop strategies to attract students, such as career consulting.
Keywords: 650; Career; COVID-19; Economics; Influencer; Student